Assessment of interoperability in cloud manufacturing. (February 2020) - Mourad, Mohamed H.; Nassehi, Aydin; Schaefer, Dirk; Newman, Stephen T.
Highlights: The aim of C-MARS was applying open standards for virtual representation of manufacturing resources and capabilities. The outlined approach embraces the integration of traditional and non-CNC traditional manufacturing components. C-MARS provides a new a methodical approach for comparison of interoperable and non-interoperable manufacturing Under certain circumstances, the interoperable cloud manufacturing is beneficial over traditional manufacturing. Abstract: Cloud manufacturing is defined as a resource sharing paradigm that provides on-demand access to a pool of manufacturing resources and capabilities aimed at utilising geographically dispersed manufacturing resources in a service-oriented manner. These services are deployed via the Industrial Internet of Things (IIoT) and its underlying IT infrastructure, architecture models, as well as data and information exchange protocols and standards. In this context, interoperability has been identified to be a key enabler for implementing such vertically or horizontally integrated cyber-physical systems for production engineering. Adopting an interoperability framework for cloud manufacturing systems enables an efficient deployment of manufacturing resources and capabilities across the production engineering life-cycle. In this paper, the authors investigate interoperability in the context of cloud manufacturing to identify the key parameters that determine whether or not a change-over from traditional cloud manufacturing to interoperable cloud manufacturing is financially viable for a given scenario of service providers and manufacturing orders. The results obtained confirm that interoperable cloud manufacturing systems cannot be considered a one-size-fits-all option. Rather, its applicability depends on a number of driving parameters that need to be analysed and interpreted to determine whether or not it provides a financially viable alternative to cloud manufacturing without an overarching interoperability framework.